Android based Parental Monitoring Apps - Abdullah, Dalilah; Mohamed, Muzaffar; Husny, Herny Ramadhani Mohd (International Journal of Engineering and Technology, 2018)
Nowadays the usage of handheld devices in a young generation were constantly increasing. Handheld devices had been involved in high profiles cases that involved children, therefore strict monitoring of childrenâ€™s devices usage are required for safety risks. This project is to develop Stealth-based Android Parental Monitoring App to help parent monitor their childâ€™s mobile activity silently. The mobile usage behavior can be analyze and then parents can plan for proactive measures to deal with the problem. This application was developed based on client server application, where Android based application is developed for client side and web application is developed on the server-side. Authentication process is required to activate the application, as only authenticated user can manage the application and at the same time, the application will run stealthily, invisible from the users. Pattern Lock and password method were used for authentication process. For the purpose of stealth process, â€œsecret doorâ€Â technique,Â whereÂ developer will disableÂ an application component;Â thisÂ techniqueÂ willÂ have the effect of removingÂ anÂ applicationÂ shortcutÂ fromÂ any Launcher. The application at android based will be able to log the location, message log, call log, network log, and device information. The collected data will be uploaded to a web server to be reviewed through the internet-enabled devices. The functionality testing were done on both Android Based client side application and web application server side web application. For client side application eight test cases were developed: Android Authentication Module, Android device registration module, Android logging module, Android uploading module, Android system cleaner module, Android stealth hide/reveal icon module, Android stealth launch application via dialer module and Android protection module. For each test case, the result is indicated as pass. For Server Side Web application, four test cases were developed; Web Application Registration Module, Web Application Authentication Module, Web Application Monitoring Module and Web Application Disconnect Device Module. For each test case, the result is indicated as pass. Android Based Parental Monitoring Apps has been successfully developed and meet the development objective to collect Android critical data including network log, call log, device information log, incoming or outgoing SMS and Call logs in stealth and synchronized it to the server where it can be used as digital evidence if necessary. The result of this project is hoped to benefits the society by providing a better monitoring technique for the concerned parent via implementing an alternate way on how to continuously collect and monitor their children/teen mobile activity.